Urban renewal and micro-dynamics of territorial valorization: a multi-scale exploration in the Technological District, Buenos Aires Autonomous City (Huellas, 2021)
As part of a set of urban renewal policies in strategic areas of the Autonomous City of Buenos Aires, in 2008 the Technological District was created; which is located in Commune 4, a south-peripheral area, historically dismissed by capital investments and by the State. This paper aims at analysing the territorial effects of the Technological District in the valorisation of the real estate market and the changes in land use. From a multi-scalar approach, it focuses in the micro-territorial scale, from the exploration of four different zones within the area of the Technological District. The qualitative-quantitative methodology was based on the analysis of the sale offers of land, apartments, storefronts and offices in the Technology District, and the changes in land use, between 2006 and 2017. The results reveal that there is an accelerated real estate and land valorisation in the Technological District in comparison with other areas in the City. However, the renewal is selective in the territory. This tends to reinforce pre-existing and unequal patterns of appreciation among the different areas of the District, which allows to qualify the “success” of the policy.
Keywords: renovación urbana – valorización territorial – mercado inmobiliario – Ciudad de Buenos Aires